2013
DOI: 10.12933/therya-13-101
|View full text |Cite
|
Sign up to set email alerts
|

Morfometría geométrica craneal en tres especies de roedores arborícolas neotropicales, género Rhipidomys (Mammalia, Rodentia, Sigmodontinae) en Venezuela

Abstract: In this study, we compared a new population of Rhipidomys from the Sierra de Aroa-Yaracuy State in Venezuela with taxa included within the R. fulviventer section sensu Tribe (1996). We used geometric morphometrics from selected landmarks on the skull, and mandible of three species of Rhipidomys, and three subspecies of R. fulviventer housed in Venezuelan museums. We grouped every taxon as R. venustus Aroa (Sierra de Aroa), R. venustus (Sistema de colinas Lara-Falcón, Cordillera Central, and Andes-Cordillera de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Based on phylogenetic reconstruction, R. albujai forms a sister clade to the group leucodactylus with a high support (0.99), so one might suggest that the species R. albujai is part of the leucodactylus section. R. albujai has not been mentioned in previous studies of Rocha et al [4], Costa et al [5], de la Sancha et al [3], and García and Gonzales [15]. This species is distributed in the Cordillera Oriental of southeastern Ecuador.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on phylogenetic reconstruction, R. albujai forms a sister clade to the group leucodactylus with a high support (0.99), so one might suggest that the species R. albujai is part of the leucodactylus section. R. albujai has not been mentioned in previous studies of Rocha et al [4], Costa et al [5], de la Sancha et al [3], and García and Gonzales [15]. This species is distributed in the Cordillera Oriental of southeastern Ecuador.…”
Section: Discussionmentioning
confidence: 87%
“…Several diagnostic characters distinguish members of this genus from other rodents in the subfamily Sigmodontinae: Wide feet with large plantar pads, dorsal surface of the feet with a dark patch, long thick tail covered in hair, generally with a tuft of longer hair at the end of the tail, short face with large eyes, and long mystacial vibrissae that pass the points of the ears reaching beyond the shoulders when angled toward the posterior [1,6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…We collected these reference samples at the Belize Zoo, from farms around the study sites, and through opportunistic sampling from road-killed animals observed during the scat surveys. We also used other reference materials to identify prey remains not accounted for in our collection (teeth and bone morphology – Engilis et al 2012, García & Sánchez-González 2013, Goodwin 1969; hair morphology – Baca Ibarra & Sanchez-Cordero 2004, Lungu et al 2007). We cleaned fragments of bone, teeth and claws and observed such remains under a dissecting microscope.…”
Section: Methodsmentioning
confidence: 99%